Diagnostic value of HE4+ circulating tumor cells in patients with suspicious ovarian cancer - Guo, Yan-Xiu (Oncotarget, 2018)
Lacking a satisfactory screening test, ovarian cancer is frequently diagnosed at a late stage, leading to poor patient outcomes. This study investigated the diagnostic value of circulating tumor cells (CTCs) in peripheral blood from patients with suspected ovarian tumors. Sixty-one women suspected of having an ovarian mass were prospectively enrolled in this study. CTCs were identified and counted using microfluidic isolation and immunofluorescent staining of CD45, HE4, and epithelial and mesenchymal (E&M) markers (epithelial cell adhesion molecule, cytokeratins, and vimentin). Thirty (49%) of the patients were diagnosed with ovarian cancer. DAPI+/E&M+/CD45-/HE4+ CTC counts were higher in these patients than in patients with benign tumors (p = 0.016). The receiver operating characteristic (ROC) curve showed that the sensitivity of CTCs was 73.3%, which was superior to that of CA125 (56.7%). In patients with elevated CA125 levels (≥35 U/ml), CTC counts still showed good specificity (86.7%). Our findings suggest the DAPI+/E&M+/CD45-/HE4+ CTC count is a useful diagnostic indicator in patients with suspected ovarian cancer.